2012
DOI: 10.1186/1746-1596-7-141
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP-2 and TIMP-1 in Renal Tissue of Patients with Chronic Active Antibody-mediated Renal Graft Rejection

Abstract: ObjectiveTo investigate the expression of matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metallopropteinase-1 (TIMP-1) in the renal allografts of patients with chronic active antibody-mediated rejection (AMR), and to explore their role in the pathogenesis of AMR.MethodsImmunohistochemistry assay and computer-assisted image analysis were used to detect the expression of MMP-2 and TIMP-1 in the renal allografts with interstitial fibrosis and tubular atrophy (IF/TA) in 46 transplant recipients and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In our previous study [27], we found that matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metalloproteinase-1 (TIMP-1) were important cytokines for ECM synthesis and degradation, and the excess accumulation of ECM is the main pathological mechanism of fibrosis in antibody-mediated renal graft rejection. Our present study reveals that TGF-beta1 induced expression of mmp-9 may induce mononuclear cells infiltration in the interstitium of allografts and SMC replication.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [27], we found that matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metalloproteinase-1 (TIMP-1) were important cytokines for ECM synthesis and degradation, and the excess accumulation of ECM is the main pathological mechanism of fibrosis in antibody-mediated renal graft rejection. Our present study reveals that TGF-beta1 induced expression of mmp-9 may induce mononuclear cells infiltration in the interstitium of allografts and SMC replication.…”
Section: Discussionmentioning
confidence: 99%
“…After PBS washes, slices were incubated with a HRP-conjugated secondary antibody at 37°C for 30 min before staining with DAB and hematoxylin. Semi-quantitative analysis of target protein expression was performed as previously described3 [24]. Briefly, ten randomly selected fields (400x) per kidney were captured and each field was imaged with one glomerulus in the center of the picture.…”
Section: Methodsmentioning
confidence: 99%
“…TIA-1 is the granule component responsible for inducing DNA fragmentation and apoptosis in cytolytic lymphocyte targets. In acute rejection after kidney transplantation, the quantity and intensity of TIA-1 expression increase, and the degree of this variation can reflect rejection severity to some extent [15,28,29]. However, the diagnostic value of TIA-1 in acute rejection after liver transplantation has not been determined.…”
Section: Discussionmentioning
confidence: 99%